Stable electrolyte compositions for electrochemical storage systems

By using a composite anode made of silicon particles and conductive additives, combined with a high-temperature pyrolysis process and a high-voltage stable electrolyte, the problem of large volume change of silicon-based anodes was solved, which improved the energy density and cycle life of lithium-ion batteries and enhanced the stability and safety of the batteries.

CN120936654APending Publication Date: 2025-11-11ENEVATE CORP
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202480018899.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-01-27
Filing Date
2024-01-26
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

Existing lithium-ion battery anode materials, especially silicon-based anodes, suffer from problems such as loss of electrical contact due to large volume changes, instability of the solid electrolyte interface, and reduced cycle life, which affect the energy density and stability of the battery.

Method used

A composite material containing silicon particles and conductive additives is used as the anode. Combined with appropriate binders and electrolytes, a self-supporting electrode is formed through a high-temperature pyrolysis process to ensure stable electrical contact and adapt to changes in silicon volume. At the same time, a high-voltage stable electrolyte is used to improve battery performance.

Benefits of technology

It improves the energy density and cycle life of lithium-ion batteries, reduces the risk of electrode material isolation, and enhances battery stability and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120936654A_ABST
    Figure CN120936654A_ABST
Patent Text Reader

Abstract

Novel electrolyte compositions for lithium ion energy storage devices with silicon-based electrode materials have improved stability. The electrolyte composition may be used in an energy storage device that includes a first electrode and a second electrode, where at least one of the first electrode and the second electrode is a silicon-based electrode; a separator between the first electrode and the second electrode; and the electrolyte composition.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-references / citations of related applications are incorporated.

[0002] N / A Technical Field

[0003] This disclosure relates to aspects of energy generation and storage. More specifically, certain embodiments of this disclosure relate to electrolytes for lithium-ion energy storage devices having silicon-based anode materials. Background Technology

[0004] Conventional methods for battery electrodes can be expensive, cumbersome, and / or inefficient; for example, they can be complex and / or time-consuming to implement and may limit battery life.

[0005] By comparing conventional and traditional methods with some aspects of this disclosure as described in the remainder of this application with reference to the accompanying drawings, further limitations and disadvantages of such a system will become apparent to those skilled in the art. Summary of the Invention

[0006] A novel electrolyte composition for improving the stability of lithium-ion energy storage devices, substantially as shown and / or described in at least one of the relevant figures, is set forth more fully in the claims.

[0007] These and other advantages, aspects and novel features of this disclosure, as well as details of the embodiments shown therein, will be more fully understood from the following description and accompanying drawings.

[0008] Brief description of several views in the accompanying drawings

[0009] Figure 1 An example battery according to an example implementation of this disclosure is shown.

[0010] Figure 2 This is a flowchart of a lamination process for forming a silicon-dominant anode cell according to an example embodiment of the present disclosure.

[0011] Figure 3 This is a flowchart of a direct coating process for forming a silicon-dominant anode cell according to an example embodiment of the present disclosure.

[0012] Figure 4 An example battery management system (BMS) for managing the operation of a battery is shown according to an example embodiment of the present disclosure.

[0013] Figure 5 The performance of different ether-based electrolytes compared to carbonate-based electrolytes according to example embodiments of this disclosure is shown.

[0014] Figure 6The normalized discharge capacity retention of a 5-layer pouch cell according to an example embodiment of the present disclosure is shown in room temperature and high temperature cycling.

[0015] Figure 7 Gas evolution analysis of a 5-layer Si / NCM811 pouch cell according to an example embodiment of the present disclosure is shown. Detailed Implementation

[0016] Figure 1 An example battery is shown. (See reference) Figure 1 The image shows a battery 100, which includes a separator 103 sandwiched between an anode 101 and a cathode 105, and current collectors 107A and 107B. A load 109 coupled to the battery 100 is also shown, illustrating the situation when the battery 100 is in a discharge mode. In this disclosure, the term "battery" can be used to refer to a single electrochemical cell, multiple electrochemical cells formed as a module, and / or multiple modules formed as a package. Furthermore, Figure 1 The battery 100 shown is a very simplified example, used only to illustrate the working principle of a lithium-ion cell. Figure 1 The right side shows an example of an actual structure where a stack of electrodes and separators is used. Except for the outermost electrode in some cases, the electrode coating is typically on both sides of the current collector. The stack can be formed into different shapes, such as button cells, cylindrical cells, prismatic pouch cells, or prismatic can cells.

[0017] The development of portable electronic devices and the electrification of transportation have driven the demand for high-performance electrochemical energy storage. In devices ranging from small-scale (< 100 Wh) to large-scale (> 10 kWh), Li-ion batteries are widely used compared to other rechargeable battery chemicals due to their advantages in energy density and cyclability.

[0018] Anode 101 and cathode 105, together with current collectors 107A and 107B, may include electrodes. These electrodes may include plates or membranes within or containing an electrolyte material. In this case, the plates may provide a physical barrier for the electrolyte and conductive contact with external structures. In other embodiments, the anode / cathode plates are immersed in an electrolyte, while a housing provides an electrolyte seal. Anode 101 and cathode 105 are electrically connected to current collectors 107A and 107B, which contain metal or other conductive materials to provide electrical contact with the electrodes and physical support for the active material during electrode formation.

[0019] Figure 1The configuration shown illustrates a battery 100 in discharge mode, whereas in a charging configuration, a charger can be used instead of a load 109 to reverse the process. In one type of battery, the separator 103 is typically a membrane material made of an electronically insulating polymer, which, for example, prevents electrons from flowing from the anode 101 to the cathode 105, or vice versa, while being porous enough to allow ions to pass through the separator 103. Typically, the separator 103, cathode 105, and anode 101 materials are formed as sheets, films, or foils coated with active materials, respectively. At this point, different methods or processes can be used to form electrodes, particularly silicon-containing and / or silicon-dominant (>50% by capacity or weight of active material) anodes. For example, lamination or direct coating can be used to form silicon-containing anodes (silicon anodes). Examples of such processes are shown in... Figure 2 and Figure 3 Shown and referenced Figure 2 and Figure 3 Description. The sheets of cathode, separator, and anode are then stacked or wound (separator 103 separates cathode 105 and anode 101) to form battery 100. In some embodiments, separator 103 is a sheet, and winding and stacking methods are typically used in its fabrication. In these methods, the anode, cathode, and current collector (e.g., electrodes) may comprise membranes.

[0020] In an example scenario, battery 100 may comprise a solid electrolyte, a liquid electrolyte, or a gel electrolyte. Separator 103 is preferably insoluble in a typical battery electrolyte, which may include, for example, compositions comprising: ethylene carbonate (EC), fluoroethylene carbonate (FEC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), etc., and dissolved LiBF4, LiAsF6, LiPF6, and LiClO4, LiFSI, LiTFSI, etc. In an example scenario, the electrolyte may comprise lithium hexafluorophosphate (LiPF6) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), which can be used together in various electrolyte solvents. Lithium hexafluorophosphate (LiPF6) may be present at a concentration of about 0.1 mol (M) to 4.0 mol (M), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) may be present at a concentration of about 0 mol (M) to 4.0 mol (M). The solvent may contain one or more cyclic carbonates, such as ethylene carbonate (EC), fluoroethylene carbonate (FEC), or propylene carbonate (PC), and linear carbonates, such as ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and dimethyl carbonate (DMC), in various percentages. In some embodiments, the electrolyte solvent may contain one or more of about 0% to 40% by weight of EC, about 2% to 40% by weight of FEC, and / or about 50% to 70% by weight of EMC.

[0021] The separator 103 can be immersed in a liquid electrolyte or a gel electrolyte. Furthermore, in the example embodiment, the separator 103 does not melt at temperatures below about 100°C to 140°C and exhibits sufficient mechanical properties for battery applications. During operation, the battery can undergo expansion and contraction of the anode 101 and / or the cathode 105. In the example embodiment, the separator 103 can expand and contract by at least about 5% to 10% without tearing or otherwise failing, and can also be flexible.

[0022] The separator 103 can be sufficiently porous to allow ions to pass through it once wetted with, for example, a liquid electrolyte or a gel electrolyte. Alternatively (or additionally), the separator can absorb electrolytes through gelation or other processes, even without significant porosity. The porosity of the separator 103 is generally not so high that electrons can be transferred between the anode 101 and the cathode 105.

[0023] Anode 101 and cathode 105 comprise electrodes for battery 100, providing electrical connection to means for transferring charge during charging and discharging. For example, anode 101 may comprise silicon, carbon, or a combination of these materials. Typical anode electrodes comprise carbon materials and current collectors such as copper sheets. Carbon is commonly used because of its excellent electrochemical properties and its electrical conductivity. Anodes currently used in rechargeable lithium-ion cells typically have a specific capacity of approximately 200 mAh / g. Graphite is the active material used for most lithium-ion battery anodes, with a theoretical energy density of 372 mAh / g. In contrast, silicon has a high theoretical capacity of 4200 mAh / g. To increase the volumetric and gravimetric energy densities of lithium-ion batteries, silicon can be used as the active material for cathode 105 or anode 101. Si anodes can be in the form of a composite on a current collector, where Si > 50% by capacity or weight in the composite layer.

[0024] In this example scenario, anode 101 and cathode 105 store ions, such as lithium ions, for charge separation. In this example, the electrolyte carries positively charged lithium ions from anode 101 to cathode 105 through separator 103 in discharge mode, as... Figure 1 As shown, and vice versa in charging mode. The movement of lithium ions and their reaction with the electrodes generate free electrons in one electrode, which in turn generates a charge at the opposite current collector. Current then flows from the current collector (where the charge is generated) through the load 109 to the other current collector. The separator 103 blocks the flow of electrons within the battery 100, allows the flow of lithium ions, and prevents direct contact between the electrodes.

[0025] When the battery 100 discharges and provides current, the anode 101 releases lithium ions to the cathode 105 through the separator 103, generating an electron flow from one side to the other via the connected load 109. When the battery is charged, the opposite occurs, in which case lithium ions are released from the cathode 105 and received by the anode 101.

[0026] The selection of materials for the anode 101 and cathode 105 is important for the reliability and potential energy density of the battery 100. Current lithium-ion batteries require improvements in energy, power, cost, and safety to compete, for example, with internal combustion engine (ICE) technology and allow for the widespread adoption of electric vehicles (EVs). High energy density and high power density of lithium-ion batteries have been achieved through the development of high-capacity and high-voltage cathodes, high-capacity anodes, and electrolytes with high voltage stability and interfacial compatibility with the electrodes. Functionally non-flammable or non-flammable electrolytes can be used to improve safety. Furthermore, materials with low toxicity are advantageous as battery materials to reduce processing costs and improve consumer safety.

[0027] While the performance of electrochemical electrodes depends on many factors, it largely depends on the robustness of the electrical contacts between electrode particles and between the current collector and electrode particles. The conductivity of silicon anode electrodes can be improved by incorporating conductive additives with different morphological properties. Carbon black (Super P), vapor-grown carbon fibers (VGCF), and mixtures of both have previously been incorporated into anodes to improve conductivity and otherwise enhance performance. The synergistic interaction between the two carbon materials can facilitate electrical contact throughout the large volumetric changes of the silicon anode during charging and discharging, and provide additional mechanical robustness and strength to the electrode (e.g., to hold the electrode material in place). These contact points (especially when using high aspect ratio conductive materials) facilitate electrical contact between the anode material and the current collector, mitigating isolation (island formation) of the electrode material while also improving conductivity between silicon regions. Graphene and carbon nanotubes can be used because they exhibit similar benefits. Therefore, in some cases, mixtures of two or more of carbon black, vapor-grown carbon fibers, graphene, and carbon nanotubes can be used independently or in combination for conductivity and other performance benefits.

[0028] Existing lithium-ion batteries typically employ graphite-dominant anodes, which are lithium-intercalation anodes. However, silicon-containing, and especially silicon-dominant, anodes offer improvements compared to graphite-dominant lithium-ion batteries. Silicon exhibits higher gravimetric capacity (4200 mAh / g vs. 372 mAh / g for graphite) and volumetric capacity (2194 mAh / L vs. 890 mAh / L for graphite). Furthermore, Si has a higher redox potential relative to Li compared to graphite, with a voltage plateau of approximately 0.3 V to 0.4 V vs. Li / Li+, allowing it to maintain an open-circuit potential that avoids undesirable Li plating and dendrite formation. While silicon exhibits excellent electrochemical activity, achieving stable cycle life for silicon-based anodes is challenging due to the large volumetric changes during lithiation and delithiation. The silicon region may lose electrical contact with the anode because the large volumetric changes, combined with its low conductivity, separate the silicon from the surrounding material within the anode.

[0029] Furthermore, large silicon volume changes exacerbate the formation of the solid electrolyte interface (SEI), which can further lead to electrical insulation and thus capacity loss. The expansion and contraction of silicon particles during charge-discharge cycles causes particle fragmentation, increasing their specific surface area. As the silicon surface area changes and increases during cycling, the SEI repeatedly disintegrates and reforms. Therefore, during cycling to a thick electronic and ionic insulating layer, the SEI continuously accumulates around the fragmented silicon regions. This accumulated SEI increases the electrode impedance and reduces the electrode's electrochemical reactivity, which is detrimental to cycle life. Therefore, silicon anodes require a highly conductive matrix that (a) holds the silicon particles together in the anode, (b) is flexible enough to accommodate the large volume expansion and contraction of silicon, and (c) allows for rapid electron conduction within the matrix.

[0030] Therefore, there are trade-offs between the functions of the active material, conductive additives, and polymer binder. The aforementioned high-energy-density silicon anode with low conductivity and large volumetric variation may adversely affect the equilibrium. The polymer binder may be pyrolyzed to produce a pyrolytic carbon matrix with embedded silicon particles. Furthermore, the polymer can be selected from polymers that are completely or partially soluble in water or other environmentally friendly solvents, or mixtures thereof. Polymer suspensions of materials insoluble in water can also be used.

[0031] In some implementations, dedicated systems and / or software can be used to control and manage the battery or its pack. In this regard, such dedicated systems may include appropriate circuitry for operating and / or performing control and management-related functions or operations. Furthermore, such software may run on appropriate circuitry, such as processing circuitry already present in the system (e.g., a general-purpose processing unit), or it may be implemented on dedicated hardware. For example, battery packs (e.g., those used in electric vehicles) may be equipped with a battery management system (BMS) for managing the battery (or pack) and its operation. Figure 4 An example battery management system (BMS) is shown and referenced. Figure 4 The example battery management system (BMS) is described in more detail.

[0032] Figure 2 This is a flowchart of an example lamination process for forming silicon-containing or silicon-dominant battery cells. The process employs a high-temperature pyrolysis process, layer removal, and lamination to adhere an active material layer to the current collector on a substrate. This strategy can also be used with other types of anodes, such as graphite, conversion anodes (e.g., transition metal oxides, transition metal phosphides), and other alloy anodes (e.g., Sn, Sb, Al, P, etc.).

[0033] To fabricate the anode, the original electrode active material is mixed in step 201. During this mixing process, the active material may be mixed with binders / resins (e.g., water-soluble PI (polyimide), PAI (polyamide-imide), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), poly(acrylic acid) (PAA), sodium alginate, phenolic resin, or other water-soluble resins and mixtures thereof), solvents, rheology modifiers, surfactants, pH modifiers, and conductive additives. The materials may include, for example, carbon nanotubes / fibers, graphene sheets, metal polymers, metals, semiconductors, and / or metal oxides. Silicon powder with particle sizes of 1 μm to 30 μm or 5 μm to 30 μm can then be dispersed, for example, at 1000 rpm in polyamic acid resin, PAI, or PI (15% to 25% solids in N-methylpyrrolidone (NMP) or deionized water (DI)) for, for example, 10 minutes. A conjugated carbon / solvent slurry can then be added and dispersed, for example, at 2000 rpm for, for, for, 10 minutes to achieve a slurry viscosity of 2000 cP to 4000 cP and a total solids content of approximately 30% to 40%. The pH of the slurry can be varied from acidic to alkaline, which may be beneficial for controlling the solubility, conformation, or adhesion behavior of water-soluble polyelectrolytes such as polyamic acid, carboxymethyl cellulose, or polyacrylic acid. Ionic or nonionic surfactants can be added to promote wetting of insoluble components of the slurry or the substrate used in the coating process. Particle size and mixing time can be varied to configure electrode coating density and / or roughness.

[0034] Furthermore, the cathode electrode coating can be mixed and applied in step 201 (e.g., applied to aluminum), wherein the electrode coating can comprise a cathode material mixed with the carbon precursor and additives as described above for the anode electrode coating. The cathode material can include lithium nickel cobalt manganese oxide (NMC (also known as NCM): LiNi x Co y Mn z O2, x+y+z=1), lithium iron phosphate (LFP: LiFePO4 / C), lithium nickel manganese spinel (LNMO: e.g. LiNi 0.5 Mn 1.5 O4), lithium nickel cobalt aluminum oxide (NCA:LiNi) a Co b Al c O2, a+b+c=1), lithium manganese oxide (LMO: e.g., LiMn2O4), lithium nickel cobalt manganese aluminum oxide (NCMA: e.g., Li[Ni 0.89 Co 0.05 Mn 0.05 Al 0.01The quaternary system of O2, lithium cobalt oxide (LCO: e.g., LiCoO2), and other Li-rich cathode or similar materials, or combinations thereof. Particle size and mixing time can be varied to configure electrode coating density and / or roughness.

[0035] In step 203, the slurry can be applied to the substrate. In this step, the slurry can be applied at, for example, a concentration of 2 mg / cm³. 2 Up to 4 mg / cm 2 The substrate is loaded and coated onto a polyester, polyethylene terephthalate (PET), or Mylar film, and then dried in step 205 to form an anode sample with a high Si content and less than 15% residual solvent content. This can be followed by an optional calendering process in step 207, where a series of hard rollers can be used to polish the film / substrate into a smooth and dense sheet of material.

[0036] In step 209, the film containing the active material can then be removed from the PET, wherein the active material layer can be peeled off from the polymer substrate. Following peeling can be a pyrolysis step 211, in which the material can be heated to, for example, 600°C to 1250°C for 1 to 3 hours, cut into sheets, and vacuum dried using a two-stage method (120°C for 15 hours, 220°C for 5 hours). If a polypropylene (PP) substrate is used, the peeling process can be skipped, and PP can leave approximately 2% char residue during pyrolysis.

[0037] In step 213, electrode material can be laminated onto the current collector. For example, a copper foil with a thickness of 5 μm to 20 μm can be used, for example, at a concentration of 0.2 mg / cm³. 2 Up to 0.6 mg / cm 2 A nominally loaded polyamide-imide coating (applied as a 6 wt% varnish in NMP and dried, for example, at 110°C under vacuum for 12 to 18 hours) is applied. The anode sample can then be laminated onto the adhesive-coated current collector. In an example case, a heated hydraulic press is used to laminate the silicon-carbon composite film onto the coated copper. An example lamination process involves 30 to 70 seconds at 300°C and 3000 to 5000 psi to form a polished silicon composite electrode.

[0038] In step 215, a battery cell can be formed. At this point, the anode can be used to assemble the cell with the cathode, separator, and electrolyte material. In some cases, a separator with significant adhesion properties can be used.

[0039] In step 217, the cell can be evaluated prior to the formation process. Measurements may include impedance values, open-circuit voltage, and electrode and cell thickness measurements. A formation cycle is defined as any type of cell subjected to charge / discharge for the purpose of producing a cell for normal cycling and is considered part of the cell manufacturing process. Different charge and discharge rates can be used in the formation step. During formation, initial lithiation of the anode can be performed, followed by delithiation. The cell may be clamped during formation and / or cycling.

[0040] Figure 3 This is a flowchart of a direct coating process for forming silicon-containing or silicon-dominant battery cells. The process involves physically mixing active materials, conductive additives, and binders, and then directly coating the mixed slurry onto a current collector prior to pyrolysis. This example process includes a direct coating process where an anode or cathode slurry is directly coated onto copper foil using binders such as CMC, SBR, PAA, sodium alginate, PAI, PI, and mixtures and combinations thereof.

[0041] In step 301, the active material may be mixed with, for example, a binder / resin (e.g., PI, PAI, or phenol), a solvent (e.g., NMP, water, other environmentally friendly solvents, or mixtures thereof), and a conductive additive. For example, the material may include carbon nanotubes / fibers, graphene sheets, metal polymers, metals, semiconductors, and / or metal oxides. For example, silicon powder having a particle size of 1 μm to 30 μm may then be dispersed at, for example, 1000 rpm in a polyamic acid resin, PAI, PI (15% solids in DI water or N-methylpyrrolidone (NMP)) for, for example, 10 minutes, and then a conjugated carbon / solvent slurry may be added and dispersed at, for example, 2000 rpm for, for, for, for, 10 minutes to achieve a slurry viscosity of 2000 cP to 4000 cP and a total solids content of approximately 30% to 40%.

[0042] Furthermore, the cathode active material can be mixed in step 301, wherein the active material may include lithium cobalt oxide (LCO), lithium iron phosphate, lithium nickel cobalt manganese oxide (NMC), lithium nickel cobalt aluminum oxide (NCA), lithium manganese oxide (LMO), lithium nickel manganese spinel or similar materials or combinations thereof mixed with the binder described above for the anode active material.

[0043] In step 303, the slurry can be coated onto the copper foil. In the direct coating process described herein, an anode slurry containing residual solvent is coated onto the current collector, followed by drying and calendering processes for densification. A pyrolysis step (~500°C to 800°C) is then performed, causing the carbon precursor to be partially or completely converted into glassy carbon or pyrolytic carbon. Similarly, for example, a cathode active material can be coated onto a foil material, such as aluminum. The active material layer can undergo a drying process in step 305 to reduce the residual solvent content. An optional calendering process can be used in step 307, where a series of hard rollers can be used to polish the film / substrate into a smoother and denser sheet of material. In step 307, the foil and coating are optionally advanced through a rolling mill for calendering, in which the surface is smoothed and the thickness is controlled to be thinner and / or more uniform.

[0044] In step 309, the active material can be pyrolyzed by heating to 500°C to 1000°C, causing the carbon precursor to be partially or completely converted into glassy carbon. Pyrolysis can be performed in a wound form or after stamping. If the electrode is pyrolyzed in a wound form, it is stamped into a single sheet after pyrolysis. The pyrolysis step can produce an anode active material having a silicon content greater than or equal to 50% by volume or by weight. In an example case, the anode active material layer can contain 20% to 95% silicon. In another example case, it can contain 50% to 95% silicon by weight. In step 311, a cell can be formed, which may also include stamping the electrodes. At this point, the formed electrodes can be stamped without pre-stamping / pre-piercing the current collector foil. For example, the formed electrodes can be pierced using a stamping roller. The stamped anode can then be used to assemble a cell with a cathode, separator, and electrolyte material. In some cases, separators with significant adhesion properties can be used.

[0045] In step 313, the cell can be evaluated prior to the formation process. Measurements may include impedance values, open-circuit voltage, and cell and / or electrode thickness. During formation, initial lithiation of the anode may be performed, followed by delithiation. The cell may be clamped during formation and / or early cycling. A formation cycle is defined as any type of charge / discharge performed for the purpose of preparing a cell for normal cycling and is considered part of the cell manufacturing process. Different charge and discharge rates may be used in the formation step.

[0046] Figure 4 An example battery management system (BMS) is shown for managing the operation of a battery. Figure 4 The Battery Management System (BMS) 400 is shown.

[0047] The battery management system (BMS) 400 may include components configured to manage one or more batteries (e.g., each is a reference). Figure 1 A suitable circuitry (e.g., processor 410) for the described example of battery 100. At this point, BMS 400 can communicate with and / or connect to each battery 100. In some embodiments, a single processor (e.g., a conventional processor, such as an electronic control unit (ECU), microcontroller unit (ECU), etc.) or several such single processors may be used and can be configured to process algorithms or control functions related to the battery. In such embodiments, such a processor may be connected to the battery, for example via processor 410, and therefore can be treated as part of BMS 400 and function as part of processor 410.

[0048] In some embodiments, battery 100 and BMS 400 can communicate with and / or be coupled to each other, for example, via electronic or wireless communication. In some embodiments, BMS 400 can be incorporated into battery 100. Alternatively, in some embodiments, BMS 400 and battery 100 can be combined into a common package 420. Furthermore, in some embodiments, BMS 400 and battery 100 can be separate devices / components and can only communicate with each other when they are in the same system. However, this disclosure is not limited to any particular arrangement.

[0049] With the increasing demand for zero-emission electric vehicles and grid-based energy storage systems, there is a strong need for lower costs and improvements in the energy density, power density, and safety of lithium (Li)-ion batteries. Achieving high energy density and safety in lithium-ion batteries requires the development of high-capacity, high-voltage cathodes, high-capacity anodes, and corresponding functional electrolytes with high voltage stability, interfacial compatibility with electrodes, and safety.

[0050] As described above, lithium-ion batteries typically include a separator and / or electrolyte between the anode and cathode. In one type of battery, the separator, cathode, and anode materials are each formed into sheets or films. The sheets of cathode, separator, and anode are then stacked or wound (where the separator separates the cathode and anode (e.g., electrodes)) to form the battery. Typical electrodes consist of layers of electrochemically active material on a conductive metal (e.g., aluminum and copper). Films can be wound or cut into blocks, and then said blocks are stacked into stacks. These stacks have alternating electrochemically active materials, with separators between them.

[0051] Due to its high specific gravimetric and volumetric capacities (discussed above) and low lithiation potential (< 0.4 V vs. Li / Li+), Si is one of the most promising anode materials for lithium-ion batteries. For anodes, silicon-based materials can provide significant improvements in energy density. However, the large volumetric expansion (e.g., >300%) during Li alloying / dealloying can lead to the decomposition of active materials and loss of conductive pathways, thus reducing battery cycle life. Furthermore, an unstable solid electrolyte interface (SEI) layer can form on the surface of the cycled anode, resulting in endless exposure of the Si particle surface to the liquid electrolyte. This leads to irreversible capacity loss per cycle due to reduction at low potentials (where the liquid electrolyte reacts with the exposed surface of the Si anode). Additionally, the oxidative instability of conventional non-aqueous electrolytes arises at voltages exceeding 4.5 V, which can lead to accelerated degradation of cycle performance. Because Si typically has a poorer cycle life compared to graphite, only small amounts of Si or Si alloys are used in conventional anode materials.

[0052] Cathode materials may include, for example, lithium nickel cobalt manganese oxide (NMC (NCM): LiNi x Co y Mn z O2, x+y+z=1); Lithium iron phosphate (LFP: LiFePO4 / C); Lithium nickel manganese spinel (LNMO: LiNi 0.5 Mn 1.5 O4); Lithium nickel cobalt aluminum oxide (NCA:LiNi) a Co b Al c O2, a+b+c=1); Lithium manganese oxide (LMO: LiMn2O4); Lithium nickel cobalt manganese aluminum oxide Li[Ni 0.89 Co 0.05 Mn 0.05 Al 0.01 The quaternary system of O2 (NCMA) and lithium cobalt oxide (LCO: LiCoO2) is used. Cathodes may exhibit poor stability and low capacity retention at high cutoff potentials. This can be attributed to the gradual shedding of unstable surface layers, continuous electrolyte decomposition, and the dissolution of transition metal ions into the electrolyte solution. Further reasons for poor performance may include: (i) structural changes from layered to spinel-type during cycling; (ii) surface side reactions caused by Mn and Ni dissolution at the graphite anode; and (iii) the oxidative instability of conventional carbonate-based electrolytes at high voltages. Some limitations of certain cathodes are high cost, low thermal stability, and rapid capacity decay at high current rates or during deep cycling.

[0053] As described above, a typical electrode includes a current collector, such as a copper sheet. Carbon, along with an inactive binder material, is deposited on the current collector. Carbon is typically used because of its excellent electrochemical properties and its conductivity. If the current collector layer (e.g., the copper layer) is removed, the carbon may not be able to mechanically support itself. Therefore, conventional electrodes require a support structure such as a current collector to function as an electrode. The electrode (e.g., anode or cathode) compositions described in this application can produce self-supporting electrodes. Since the conductive carbonized polymer is used for current collection in the anode structure and for mechanical support, the need for a metal foil current collector is eliminated or minimized.

[0054] To increase the volumetric and gravimetric energy densities of lithium-ion batteries, silicon can be used as the active material for either the cathode or anode. Several types of silicon materials, such as silicon nanopowders, silicon nanofibers, porous silicon, and ball-milled silicon, have also been reported as viable candidates for active materials for either the anode or cathode. Small particle sizes (e.g., nanometer-scale sizes) generally improve cycle life performance. They may also exhibit very high initial irreversible capacity. However, small particle sizes can also lead to very low volumetric energy densities (e.g., for the entire cell stack) due to the difficulty of packaging the active material. Larger particle sizes (e.g., micrometer-scale sizes) generally produce anode materials with higher densities. However, the expansion of silicon active materials due to particle breakage can lead to poor cycle life. For example, silicon can expand by more than 300% once lithium is inserted. Due to this expansion, the expansion of the silicon-containing anode should be allowed while maintaining electrical contact between silicon particles.

[0055] In some embodiments, the maximum size of the silicon particles can be less than about 40 μm, less than about 1 μm, about 10 nm to about 40 μm, about 10 nm to about 1 μm, less than about 500 nm, less than about 100 nm, and about 100 nm. All, substantially all, or at least some of the silicon particles may include the aforementioned maximum sizes. For example, the average or median maximum size of the silicon particles can be less than about 40 μm, less than about 1 μm, about 10 nm to about 40 μm, about 10 nm to about 1 μm, less than about 500 nm, less than about 100 nm, and about 100 nm.

[0056] By weight, the amount of silicon in the composite material can be greater than 0% of the mixture and the composite material. In some embodiments, the mixture contains a certain amount of silicon, said amount being from about 0% by weight to about 95% by weight of the mixture, including from about 30% by weight to about 95% by weight. The amount of silicon in the composite material can be from about 0% by weight to about 35% by weight, including from about 0% by weight to about 25% by weight, from about 10% by weight to about 35% by weight, and about 20% by weight. In further embodiments, the amount of silicon in the mixture is at least about 30% by weight; greater than 0% by weight and less than about 95% by weight; or from about 50% by weight to about 95% by weight (i.e., silicon is dominant).

[0057] Other embodiments of the amount of silicon in the electrode material (active material) include about 30% to about 95% by weight, about 50% to about 85% by weight, and about 75% to about 95% by weight. In other embodiments, the amount of silicon in the electrode material may be at least about 30% by weight; greater than 0% by weight and less than about 95% by weight; or about 50% by weight to about 95% by weight.

[0058] Further embodiments include a certain percentage of silicon, wherein the electrode material primarily comprises silicon. In some embodiments, the amount of silicon may be greater than about 95%; or about 95% to 100%. In further embodiments, the amount of silicon in the electrode material (active material) is about 96%, 97%, 98%, or 99%.

[0059] Furthermore, the silicon particles may be pure silicon or not. For example, the silicon particles may be essentially silicon or may be a silicon alloy. In one embodiment, the silicon alloy comprises silicon as the main component, as well as one or more other elements.

[0060] As described herein, micron-sized silicon particles can provide good volumetric and gravimetric energy densities, as well as good cycle life. In some embodiments, to obtain the benefits of micron-sized silicon particles (e.g., high energy density) and nano-sized silicon particles (e.g., good cycling performance), the silicon particles can have an average particle size in the micron range and a surface incorporating nanoscale features. In some embodiments, the silicon particles have an average particle size (e.g., average diameter or average maximum size) of about 0.1 μm to about 30 μm or all values ​​from about 0.1 μm to a maximum of about 30 μm. For example, silicon particles can have average particle sizes of about 0.5 μm to about 25 μm, about 0.5 μm to about 20 μm, about 0.5 μm to about 15 μm, about 0.5 μm to about 10 μm, about 0.5 μm to about 5 μm, about 0.5 μm to about 2 μm, about 1 μm to about 20 μm, about 1 μm to about 15 μm, about 1 μm to about 10 μm, about 5 μm to about 20 μm, etc. Therefore, the average particle size can be any value from about 0.1 μm to about 30 μm, for example, 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm and 30 μm.

[0061] The cathode electrode (positive electrode) described herein may comprise metal oxide cathode materials, such as lithium cobalt oxide (LiCoO2) (LCO), Ni-rich oxides, high-voltage cathode materials, lithium-rich oxides, nickel-rich layered oxides, lithium-rich layered oxides, high-voltage spinel-type oxides, and high-voltage polyanionic compounds. Ni-rich oxides and / or high-voltage cathode materials may include NCM, NCMA, and NCA. Examples of NCM materials include, but are not limited to, LiNi. 0.6 Co 0.2 Mn 0.2 O2 (NCM-622) and LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM-811). Lithium-rich oxides may include xLi2Mn3O2(1-x)LiNi a Co b Mn c O2. Nickel-rich layered oxides may include LiNi. 1+x M 1-x O z (Where M = Co, Mn, or Al). Lithium-rich layered oxides may include LiNi. 1+ x M 1-x O2 (where M = Co, Mn, or Ni). High-voltage spinel oxides may include LiNi.0.5 Mn 1.5 O4. High-voltage polyanionic compounds can include phosphates, sulfates, silicates, etc.

[0062] In some embodiments, the positive electrode can be one of NCA, NCM, NMCA, LMO, or LCO. NCM cathodes include NCM9 0.5 0.5, NCM811, NCM622, NCM532, NCM433, NCM111, etc. In a further embodiment, the positive electrode comprises a lithium-rich layered oxide xLi2MnO3·(1-x)LiNi. a Co b Mn c O2; Nickel-rich layered oxide LiNi 1-x M x O2 (M = Co, Mn and Al); or lithium-rich layered oxides LiNi 1+x M 1-x O2 (M = Co, Mn, and Ni) cathode. In some embodiments, the disclosed solvent system is used for Si-dominant anodes / / LiCoO2 (LCO), LiNi x Co y Mn z O2 (NCM, 0≤x, y, z≤1) or LiNi x Co y Al z All cells with O2 (NCA, 0≤ x, y, z≤ 1) cathode.

[0063] As mentioned above, lithium-ion batteries are widely used in the electric vehicle market and stationary energy storage devices. To further improve cell energy density, high-voltage layered transition metal oxide cathodes and high-capacity, low-voltage anodes can be used. Examples of high-voltage layered transition metal oxide cathodes include Ni-rich cathodes (e.g., NCA, NCM) and Li-rich cathodes, while high-capacity, low-voltage anodes include Si, Ge, etc. However, overall cell performance degradation (where these oxides are paired with Si or other high-capacity anodes) increases significantly above 4.30 V, limiting their wider use as high-energy cathode materials. Electrolyte decomposition at the electrolyte / electrode interface can lead to the accumulation of decomposed adducts on the NCM cathode surface. This hinders Li+ migration between the electrolyte and electrode, resulting in rapid degradation of cycle performance. Therefore, the practical integration of silicon anodes in lithium-ion batteries faces challenges such as large volume changes, unstable solid-electrolyte interfaces, and electrolyte drying.

[0064] One strategy to overcome these obstacles involves exploring new electrolyte compositions to make good use of Si-based all-cell batteries. The electrolyte composition should facilitate the formation of a uniform and stable SEI layer on the Si anode surface. This layer should have low impedance and be electronically insulating, but ionicly conductive to Li ions. Additionally, the SEI layer should possess excellent elasticity and mechanical strength to overcome the problems of Si anode volume expansion and contraction. On the cathode side, the ideal electrolyte composition should preferentially oxidize solvent molecules in the bulk electrolyte, thereby forming a protective cathode electrolyte interface (CEI) film on the cathode surface. Simultaneously, it should help mitigate transition metal ion dissolution and reduce surface resistance on the cathode side. Furthermore, the physical properties of the electrolyte can also be improved, such as ionic conductivity, viscosity, and wettability.

[0065] Therefore, this paper describes next-generation electrolyte compositions. These materials can help modify cathode surfaces to form a stable CEI layer, or form a stable, electronically insulating but ionicly conductive SEI layer on Si anode surfaces. When cycling at higher voltages, these materials can also improve the electrochemical stability of lithium-ion batteries and contribute to their calendar life. Furthermore, to mitigate battery safety concerns, these materials can impart increased thermal stability to the organic components of the electrolyte, driving up the flash point of the electrolyte formulation, increasing flame retardant effectiveness, and enhancing the thermal stability of the SEI or CEI layer on the electrode surface. In addition, the materials can provide one or more of the following benefits: increased cycle life, increased energy density, increased safety, reduced electrolyte consumption, and / or reduced gas evolution.

[0066] Electrolyte compositions for lithium-ion batteries may contain one or more solvents, one or more lithium-ion sources (e.g., lithium-containing salts), and optionally additives. The electrolyte composition may be selected to provide a lithium-ion battery with improved performance. In some embodiments, the electrolyte may contain electrolyte additives. As described herein, a lithium-ion battery may include a first electrode, a second electrode, a separator between the first and second electrodes, and an electrolyte in contact with the first electrode, the second electrode, and the separator. The electrolyte is used to facilitate ion transport between the first and second electrodes. In some embodiments, the first and second electrodes may refer to an anode and a cathode, or a cathode and an anode, respectively. The electrolyte and / or electrolyte composition may be a liquid, a solid, or a gel.

[0067] In lithium-ion batteries, the most widely used electrolyte composition is a non-aqueous liquid electrolyte; these may contain lithium-containing salts (such as LiPF6) and low molecular weight carbonate solvents, as well as various small amounts of functional additives.

[0068] In some embodiments, the electrolyte may contain more than one solvent. For example, the electrolyte may contain two or more co-solvents. In some embodiments, the co-solvent may be selected from FEC, ethyl methyl carbonate (EMC), 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether, ethylene difluorocarbonate (F2EC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), propylene carbonate (PC), dimethoxyethane (DME), γ-butyrolactone (GBL), methyl acetate (MA), ethyl acetate (EA), methyl propionate, trans-butenyl carbonate (t-BC), methyl propyl carbonate (PMC), etc.

[0069] In some embodiments, at least one of the co-solvents in the electrolyte is a fluorinated compound. In some embodiments, the fluorinated compound may be fluoroethylene carbonate (FEC) or difluoroethylene carbonate (F2EC). In some embodiments, the electrolyte contains FEC. In some embodiments, the electrolyte contains EMC and FEC. In some embodiments, the electrolyte may also contain 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether, EC, DEC, DMC, PC, GBL, and / or F2EC, or some partially or fully fluorinated linear or cyclic carbonates, ethers, etc., as a co-solvent. In some embodiments, the electrolyte contains no or substantially no fluorinated cyclic carbonates such as EC, GBL, and PC.

[0070] In some embodiments, the electrolyte for lithium-ion batteries may contain one or more solvents, said solvents containing fluorinated components, such as fluorinated cyclic carbonates, fluorinated linear carbonates, and / or fluorinated ethers.

[0071] In a further embodiment, the electrolyte solvent may be composed of cyclic carbonates, linear carbonates, or other solvents, such as fluoroethylene carbonate (FEC), difluoroethylene carbonate (DiFEC), propylene trifluorocarbonate (TFPC), ethylene carbonate (EC), propylene carbonate (PC), etc.; linear carbonates such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), etc.; and other solvents such as methyl acetate, ethyl acetate, or γ-butyrolactone, dimethoxyethane, 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether, etc.

[0072] In some embodiments, the electrolyte composition may comprise a solvent system (i.e., a solvent plus one or more co-solvents). The solvent may be fluorinated or non-fluorinated. In some embodiments, the co-solvent may be one or more linear carbonates, lactones, ethers, sulfonamides, acetates, propionates, and / or non-linear carbonates.

[0073] As used herein, the co-solvent in the electrolyte composition has a concentration of at least about 10% by volume (vol%). In some embodiments, the co-solvent of the electrolyte may be about 20 vol%, about 40 vol%, about 60 vol%, about 80 vol%, or about 90 vol% of the electrolyte composition. In some embodiments, the co-solvent may have a concentration of about 10 vol% to about 90 vol%, about 10 vol% to about 80 vol%, about 10 vol% to about 60 vol%, about 20 vol% to about 60 vol%, about 20 vol% to about 50 vol%, about 30 vol% to about 60 vol%, or about 30 vol% to about 50 vol%. The co-solvent may also be expressed as a weight percentage, in which case the co-solvent in the electrolyte composition has a concentration of at least about 10% by weight (wt%). In some embodiments, the co-solvent of the electrolyte may be about 20 wt%, about 40 wt%, about 60 wt%, about 80 wt%, or about 90 wt% of the electrolyte composition. In some embodiments, the co-solvent may have a concentration of about 10 wt% to about 90 wt%, about 10 wt% to about 80 wt%, about 10 wt% to about 60 wt%, about 20 wt% to about 60 wt%, about 20 wt% to about 50 wt%, about 30 wt% to about 60 wt%, or about 30 wt% to about 50 wt%. The amount can be measured as a percentage of the total solvent.

[0074] In some embodiments, the electrolyte composition is substantially free of cyclic carbonates other than fluorinated cyclic carbonates (i.e., fluorine-free cyclic carbonates). Examples of fluorine-free carbonates include EC, PC, GBL, and vinylene carbonate (VC). In one embodiment, the electrolyte composition is substantially free of EC.

[0075] In some embodiments, the electrolyte composition may further comprise one or more additives that impart desired properties to the mixture. An additive in an electrolyte refers to a component comprising less than 30% by weight (wt%) of the electrolyte; in some embodiments, the additive comprises less than 10% by weight (wt%) of the electrolyte. In some embodiments, the amount of each additive in the electrolyte may be from about 0.2 wt% to about 1 wt%, from 0.1 wt% to about 2 wt%, from 0.2 wt% to about 9 wt%, from about 0.5 wt% to about 9 wt%, from about 1 wt% to about 9 wt%, from about 1 wt% to about 8 wt%, from about 1 wt% to about 8 wt%, from about 1 wt% to about 7 wt%, from about 1 wt% to about 6 wt%, from about 1 wt% to about 5 wt%, from about 2 wt% to about 5 wt%, or any value between these values. In some embodiments, the total amount of the additive may be from about 1 wt% to about 9 wt%, from about 1 wt% to about 8 wt%, from about 1 wt% to about 7 wt%, from about 2 wt% to about 7 wt%, or any value between these values. In a further embodiment, the electrolyte composition may contain less than 1 wt% or less of the compound as an additive; in other embodiments, it may contain about 0.5 wt% or less or about 0.2 wt% or less. In some embodiments, the additive may be present in up to 30 wt%; in some embodiments, the additive is present in amounts from about 0.1 wt% to 30 wt%; from about 0.1 wt% to 20 wt% or from 0.1 wt% to 10%. In some embodiments, the percentage of the additive may be expressed as a volume percentage (vol%) or wt / vol%.

[0076] In some embodiments, SEI-forming additives may be added. These SEI-forming additives include, but are not limited to, FEC (fluoroethylene carbonate), VC (ethylene carbonate), VEC (vinyl ethylene carbonate), PS (1,3-propanesulfonate lactone), PES (propen-1-ene-1,3-sulfonate lactone), MMDS (methylene methanedisulfonate), TMSP (tris(trimethylsilyl)phosphite), TMS (trimethylene sulfate), TMSO (3-trimethylsilyl-2-oxazolidinone), 1,4-BS (1,4-butanesulfonate lactone), PMS (propargyl methanesulfonate), BP (biphenyl), DTD (1,3,2-dioxazothiophene-2,2-dioxide), TAP (tracelyl phosphate), etc. These additives may be present in amounts from about 0.1% to 30% by weight; from about 0.1% to 20% by weight; or from 0.1% to 10% by weight.

[0077] In some embodiments, if the solvent is present in an amount of less than 10%, it can act as an additive rather than a co-solvent. The solvent as an additive can be present at concentrations as listed above (as low as 0.1 wt%). The same material can also act as a co-solvent at higher concentrations. In some embodiments, the components of the electrolyte composition can be present in an amount of about 0.1 wt% to about 80 wt%. In other embodiments, the components can be present in an amount of about 0.1 wt% to about 60 wt%; about 0.1 wt% to about 40 wt%; about 0.1 wt% to about 20 wt%; or about 0.1 wt% to about 10 wt% or less.

[0078] In some embodiments, the electrolyte composition may contain a solvent as an additional component. In some embodiments, the additional component may be one or more solvents, including but not limited to EC (ethylene carbonate), FEC (fluoroethylene carbonate), PC (propylene carbonate), EMC (ethyl methyl carbonate), DMC (dimethyl carbonate), DEC (diethyl carbonate), GBL (gamma-butyrolactone), MA (methyl acetate), EA (ethyl acetate), t-BC (trans-butenyl carbonate), PMC (propyl methyl carbonate), etc. In some embodiments, the additional component solvent of the electrolyte composition may be present in an amount from about 0.1 wt% to about 80 wt%. In other embodiments, the component may be present in an amount from about 0.1 wt% to about 60 wt%; from about 0.1 wt% to about 40 wt%; from about 0.1 wt% to about 20 wt%; or from about 0.1 wt% to about 10 wt% or less.

[0079] In some embodiments, the electrolyte composition may comprise one or more salts, such as lithium-containing salts. Lithium-containing salts for lithium-ion batteries may include fluorinated or non-fluorinated salts. In further embodiments, lithium-containing salts for lithium-ion batteries may include lithium hexafluorophosphate (LiPF6), lithium nitrate (LiNO3), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate monohydrate (LiAsF6), lithium perchlorate (LiClO4), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(oxalate)borate (LiBOB), lithium difluoro(oxalate)borate (LiDFOB), and lithium trifluoromethanesulfonate (LiCF). The lithium-ion battery may contain one or more of the following: lithium tetrafluorooxalate phosphate (LTFOP), lithium difluorophosphate (LiPO2F2), lithium pentafluoroethyl trifluoroborate (LiFAB), lithium 2-trifluoromethyl-4,5-dicyanimidazolium (LiTDI), lithium bis(2-fluoromalonic acid)borate (LiBFMB), lithium 4-pyridyltrimethylborate (LPTB), lithium 2-fluorophenoltrimethylborate (LFPTB), lithium catechol dimethylborate (LiCDMB), lithium tetrafluorooxalate phosphate (LiFOP), etc. In some embodiments, the lithium-containing salt for use in the lithium-ion battery may include lithium hexafluorophosphate (LiPF6). In some embodiments, the electrolyte may have a salt concentration of about 1 mol / L (M). In other embodiments, the salt concentration may be higher than 1 M; or the salt concentration may be higher than 1.2 M, 1.5 M, 2 M, 3 M, or 4 M or greater. The salt weight percentage in the electrolyte composition can be as high as about 25% by weight (in some embodiments, it can be from about 10 wt% to 20 wt%), with the solvent making up the remaining weight. In some embodiments, the salt concentration can be less than 1 M, for example, from 0.1 M to 0.7 M. When using two or more salts (one can be the main component and the other can be the minor component), a lower concentration range is useful.

[0080] In some embodiments, the salt may be one or more of lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium nitrate (LiNO3), lithium perchlorate (LiClO4), lithium difluoro(oxalate)borate (LiDFOB), and / or lithium bis(oxalate)borate (LiBOB). In other embodiments, the salt may be one or more of lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluorophosphate (LiPF6), lithium nitrate (LiNO3), lithium difluoro(oxalate)borate (LiDFOB), and / or lithium bis(oxalate)borate (LiBOB). The salt concentration may be 0.5 M, 0.8 M, 1 M, 1.2 M, 1.5 M, 2 M, 3 M, or 4 M or higher. In some embodiments, the concentration is less than 1 M, for example, from 0.1 M to 0.7 M. When using two or more salts (one of which can be the primary component and the other a secondary component), a lower concentration range is useful when one can be the primary component and the other a secondary component.

[0081] Most lithium-ion cells use carbonate-based electrolytes as described above. Carbonate-based electrolytes have been developed and optimized for lithium-ion cells using graphite anodes. However, they tend to exhibit poor cycle performance when used with high-capacity anode active materials such as silicon or lithium metal.

[0082] This disclosure describes the use of ether and / or sulfonamide solvents in electrolyte compositions. Ethers and sulfonamide solvents are more suitable alternatives to carbonates due to their lower reduction potentials. However, commonly used ethers such as DME, dimethyl glycol ether, and dioxolane also have low oxidation potentials (~3.9V), making them incompatible with high-voltage cathodes such as NCMA, NCA, and NCM. This document discloses novel ether-based electrolytes and sulfonamide-based electrolytes with higher oxidation potentials, which are compatible with both high-voltage cathodes and high-capacity anodes such as Si, SiOx, or Li metals.

[0083] The electrolyte composition may contain ether and / or sulfonamide solvents, as described herein. In some embodiments, the electrolyte composition may contain ether and / or sulfonamide solvents at a concentration of at least 10 vol%. In some embodiments, the solvent of the electrolyte may be about 20 vol%, about 30 vol%, about 40 vol%, about 50 vol%, about 60 vol%, about 70 vol%, about 80 vol%, or about 90 vol%. In other embodiments, the solvent of the electrolyte may be about 10 vol% to about 90 vol%, about 10 vol% to about 80 vol%, about 10 vol% to about 60 vol%, about 20 vol% to about 60 vol%, about 20 vol% to about 50 vol%, about 30 vol% to about 60 vol%, about 30 vol% to about 70 vol%, or about 30 vol% to about 50 vol%. The solvent may also be expressed as a weight percentage, in which case the solvent in the electrolyte composition has a concentration of at least about 10% by weight (wt%). In some embodiments, the solvent for the electrolyte may be about 20 wt%, about 30 wt%, about 40 wt%, about 50 wt%, about 60 wt%, about 70 wt%, about 80 wt%, or about 90 wt% of the electrolyte composition. In some embodiments, the solvent may have a concentration of about 10 wt% to about 90 wt%, about 10 wt% to about 80 wt%, about 10 wt% to about 60 wt%, about 20 wt% to about 60 wt%, about 20 wt% to about 50 wt%, about 30 wt% to about 60 wt%, about 30 wt% to about 70 wt%, or about 30 wt% to about 50 wt%. The amount may be measured as a percentage of the total solvent.

[0084] Example structures of ether and sulfonamide solvents are shown below.

[0085] The term "alkyl" refers to a saturated aliphatic group with a straight or branched chain having the indicated number of carbon atoms. The alkyl moiety can be branched or straight-chain. For example, C1 to C6 alkyl groups include, but are not limited to, methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, isopentyl, hexyl, etc. Other alkyl groups include, but are not limited to, heptyl, octyl, nonyl, decyl, etc. Alkyl groups can include any number of carbons, such as 1 to 2, 1 to 3, 1 to 4, 1 to 5, 1 to 6, 1 to 7, 1 to 8, 1 to 9, 1 to 10, 1 to 11, 1 to 12, 2 to 3, 2 to 4, 2 to 5, 2 to 6, 3 to 4, 3 to 5, 3 to 6, 4 to 5, 4 to 6, and 5 to 6. Alkyl groups are typically monovalent, but can be divalent, for example, when the alkyl group links two moieties together.

[0086] The term "fluoroalkyl" refers to an alkyl group in which one, some, or all of the hydrogen atoms have been replaced by fluorine.

[0087] The term "alkylene" refers to an alkyl group as defined above, i.e., a divalent hydrocarbon group, attached to at least two other groups. The two parts attached to the alkylene group can be connected to the same or different atoms of the alkylene group. For example, a straight-chain alkylene group can be -(CH2). n - a divalent group, wherein n is 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10. Alkylene groups include, but are not limited to, methylene, ethylene, propylene, isopropylene, butylene, isobutylene, sec-butylene, pentylene, and hexylene.

[0088] The term "alkoxy group" refers to an alkyl group having an oxygen atom that connects the alkoxy group to a junction or to the two carbons connected to the alkoxy group. Alkoxy groups include, for example, methoxy, ethoxy, propoxy, isopropoxy, butoxy, 2-butoxy, isobutoxy, sec-butoxy, tert-butoxy, pentoxy, hexoxy, etc. Alkoxy groups can also be substituted with the various substituents described above. For example, an alkoxy group can be substituted with a halogen to form a "haloalkoxy" group, or substituted with fluorine to form a "fluoroalkoxy" group.

[0089] The term "alkenyl" refers to a straight-chain or branched hydrocarbon having 2 to 6 carbon atoms and having at least one double bond. Examples of alkenyl groups include, but are not limited to, vinyl, propenyl, isopropenyl, 1-butenyl, 2-butenyl, isobutenyl, butadienyl, 1-pentenyl, 2-pentenyl, isopentenyl, 1,3-pentadienyl, 1,4-pentadienyl, 1-hexenyl, 2-hexenyl, 3-hexenyl, 1,3-hexadienyl, 1,4-hexadienyl, 1,5-hexadienyl, 2,4-hexadienyl, or 1,3,5-hextrienyl. Alkenyl groups may also have 2 to 3, 2 to 4, 2 to 5, 3 to 4, 3 to 5, 3 to 6, 4 to 5, 4 to 6, and 5 to 6 carbon atoms. Alkenyl groups are usually monovalent, but can be divalent, for example, when an alkenyl group connects two parts together.

[0090] The term "alkenyl" refers to an alkenyl group as defined above, i.e., a divalent hydrocarbon group, that is, a group attached to at least two other groups. The two parts attached to the alkenyl group can be attached to the same or different atoms of the alkenyl group. Alkenyl groups include, but are not limited to, vinylene, propene, isopropene, butene, isobutylene, sec-butene, pentenene, and hexene.

[0091] The term "alkynyl" refers to a straight-chain or branched hydrocarbon having 2 to 6 carbon atoms and having at least one triple bond. Examples of alkynyl groups include, but are not limited to, ethynyl, propynyl, 1-butynyl, 2-butynyl, isobutynyl, sec-butynyl, butyrynyl, 1-pentynyl, 2-pentynyl, isopentenynyl, 1,3-pentadiynyl, 1,4-pentadiynyl, 1-hexynyl, 2-hexynyl, 3-hexynyl, 1,3-hexadiynyl, 1,4-hexadiynyl, 1,5-hexadiynyl, 2,4-hexadiynyl, or 1,3,5-hextriynyl. Alynyl groups may also have 2 to 3, 2 to 4, 2 to 5, 3 to 4, 3 to 5, 3 to 6, 4 to 5, 4 to 6, and 5 to 6 carbon atoms. The alkynyl group is usually monovalent, but it can be divalent, for example, when the alkynyl group connects two parts together.

[0092] The term "ynynyl" refers to an ynyl group as defined above, i.e., a divalent hydrocarbon group, that is, a group attached to at least two other groups. The two parts attached to the ynynyl group can be attached to the same or different atoms of the ynynyl group. Iynyl groups include, but are not limited to, ethynylene, propynylene, butynylene, sec-butynylene, pentyynylene, and hexynylene.

[0093] The term "cycloalkyl" refers to a saturated or partially unsaturated monocyclic, fused bicyclic, bridged polycyclic, or spirocyclic assembly containing 3 to 12, 3 to 10, or 3 to 7 ring atoms, or the indicated number of atoms. Monocyclic rings include, for example, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, and cyclooctyl. Bicyclic and polycyclic rings include, for example, norbornane, decahydronaphthalene, and adamantane. For example, C3 to C8 cycloalkyl groups include cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cyclooctyl, and norbornane. As used herein, the term "fused" refers to two rings having two shared atoms and one bond. For example, in the following structure, ring A and ring B are fused. As used herein, the term "bridged polycyclic" refers to a compound in which the cycloalkyl group contains one or more atoms that link non-adjacent atoms. The following structures... and Examples of “bridged” rings. As used herein, the term “spirocyclic” refers to two rings having a common atom and not being connected by a bridge. Examples of fused cycloalkyl groups are decahydronaphthyl, dodecahydro-1H-phenarenyl, and tetradecahydroanthrayl; examples of bridged cycloalkyl groups are bicyclo[1.1.1]pentyl, adamantyl, and norbornyl; and examples of spirocyclic cycloalkyl groups include spiro[3.3]heptane and spiro[4.5]decane.

[0094] The term "cycloalkylene" refers to a cycloalkyl group as defined above, i.e., a divalent hydrocarbon group, that is, a group attached to at least two other groups. The two parts attached to the cycloalkylene group can be attached to the same atoms or different atoms of the cycloalkylene group. Cycloalkylene groups include, but are not limited to, cyclopropylene, cyclobutylene, cyclopentylene, cyclohexylene, and cyclooctylene.

[0095] The term "aryl" refers to an aromatic ring assembly containing 6 to 16 ring carbon atoms, either monocyclic or fused bicyclic, tricyclic, or more rings. For example, the aryl group can be phenyl, benzyl, or naphthyl, preferably phenyl. The aryl group can include fused polycyclic assemblies, wherein only one ring in the polycyclic assembly is aromatic. The aryl group can be monosubstituted, disubstituted, or trisubstituted by one, two, or three groups. Naphthyl, phenyl, or phenyl monosubstituted or disubstituted with alkoxy, phenyl, halogen, alkyl, or trifluoromethyl groups are preferred as aryl groups, especially phenyl or phenyl monosubstituted or disubstituted with alkoxy, halogen, or trifluoromethyl groups, and particularly phenyl.

[0096] The term "arylene" refers to an aryl group as defined above, which is attached to at least two other groups. The two parts attached to the arylene are connected to different atoms of the arylene. The arylene group includes, but is not limited to, phenylene.

[0097] The term "heteroaryl" refers to a monocyclic or fused bicyclic or tricyclic aromatic assembly containing 5 to 16 ring atoms, wherein 1 to 4 ring atoms are heteroatoms, such as N, O, or S. For example, heteroaryl includes pyridinyl, indolyl, indazole, quinoxalinyl, quinolinyl, isoquinolinyl, benzothiopheneyl, benzofuranyl, furanyl, pyrroleyl, thiazolyl, benzothiazolyl, oxazolyl, isoxazolyl, triazolyl, tetrazolyl, pyrazolyl, imidazolyl, thiopheneyl, or any other group substituted, especially monosubstituted or disubstituted, with a group such as an alkyl, nitro, or halogen. Pyridinyl represents 2-, 3-, or 4-pyridinyl, advantageously 2- or 3-pyridinyl. Thiopheneyl represents 2- or 3-thiopheneyl. Quinolinyl preferably represents 2-, 3-, or 4-quinolinyl. Isoquinolinyl preferably represents 1-, 3-, or 4-isoquinolinyl. Benzopyranyl and benzothiaranyl preferably represent 3-benzopyranyl or 3-benzothiaranyl, respectively. Thiazolyl preferably represents 2- or 4-thiazolyl, and most preferably 4-thiazolyl. Triazolyl is preferably 1-, 2-, or 5-(1,2,4-triazolyl). Tetrazolyl is preferably 5-tetrazolyl.

[0098] Preferably, the heteroaryl group is pyridyl, indolyl, quinolinyl, pyrroleyl, thiazolyl, isoxazolyl, triazolyl, tetrazolyl, pyrazolyl, imidazolyl, thiophenyl, furanyl, benzothiazolyl, benzofuranyl, isoquinolinyl, benzothiaphenyl, oxazolyl, indazoleyl, or any substituted group, especially monosubstituted or disubstituted.

[0099] The term "heteroalkyl" refers to an alkyl group having one to three heteroatoms, such as N, O, and S. Heteroatoms can also be oxidized, for example, but not limited to -S(O)- and -S(O)2-. For example, heteroalkyl can include ethers, thioethers, alkyl-amines, and alkyl-thiols.

[0100] The term "heteroalkylene" refers to a heteroalkylene group as defined above, which is attached to at least two other groups. The two parts attached to the heteroalkylene group can be attached to the same atoms or different atoms of the heteroalkylene group.

[0101] The term "heterocyclic alkyl" refers to a cyclic system having 3 to about 20 ring members and 1 to about 5 heteroatoms such as N, O, and S. Heteroatoms can also be oxidized, for example, but not limited to -S(O)- and -S(O)2-. For example, heterocycles include, but are not limited to, tetrahydrofuranyl, tetrahydrothiophenyl, morpholinyl, pyrrolyl, pyrrolinyl, imidazoalkyl, imidazolinyl, pyrazolyl, pyrazolinyl, piperazinyl, piperidinyl, indolinyl, quininecycloyl, and 1,4-dioxa-8-aza-spiro[4.5]dec-8-yl.

[0102] The term "heterocyclic alkyl" refers to a heterocyclic alkyl group as defined above, which is attached to at least two other groups. The two parts attached to the heterocyclic alkyl group can be attached to the same atoms or different atoms of the heterocyclic alkyl group.

[0103] The term "optionally substituted" is used herein to refer to a portion that may be unsubstituted or substituted by one or more substituents. When the term "part" is used without specifically indicating that it is substituted, the part is unsubstituted.

[0104] According to this disclosure, various ether and sulfonamide solvents can be used in electrolyte compositions.

[0105] Examples of ether solvents include, but are not limited to, cyclic ether compounds of formula (1) or formula (2):

[0106] (1) or (2).

[0107] In some implementation schemes, R1 to R 10 The components can be the same or different and can be selected from H, F, CF3 and / or C1-C10 alkyl groups, wherein the C1-C10 alkyl groups can optionally be substituted. In other embodiments, R1 is F; and R2 to R 10 It can be H, F, CF3, or C1-C10 alkyl, and the C1-C10 alkyl group can optionally be substituted. Exemplary ether solvents include tetrahydrofuran (THF), 2-fluorotetrahydrofuran (THF-1F), tetrahydropyran (THP), and 2-fluorotetrahydropyran (THP-1F), as follows:

[0108] Tetrahydrofuran (THF)

[0109] 2-Fluoro-tetrahydrofuran (THF-1F)

[0110] Tetrahydropyran (THP)

[0111] 2-Fluoro-tetrahydropyran (THP-1F).

[0112] Straight-chain ethers may also be used; examples of straight-chain ether solvents include, but are not limited to, ether compounds of formula (3) or (4):

[0113] (3) or (4).

[0114] In some embodiments, R1 to R4 may be the same or different and may be selected from H, F, CF3 and / or C1-C10 alkyl groups, which may optionally be substituted. In further embodiments, R4 may be a straight-chain or branched C1-C10 alkyl group, which may be substituted with H, F, or CF3. In other embodiments, R4 may be a partially or fully fluorinated (H replaced by F) straight-chain or branched C1-C10 alkyl group, wherein all substituents are H or F.

[0115] Exemplary straight-chain ether compounds include, but are not limited to, the following straight-chain fluoroethers: and / or .

[0116] Certain straight-chain ethers (ethylene glycol ethers; also known as ethylene glycol dimethyl ethers) may also be used; ethylene glycol dimethyl ether compounds include, but are not limited to, the following formulas (5), (6) and / or (7): , (5) (6)

[0118] and / or

[0119] (7).

[0120] In equation (7), each R can be the same or different and can be selected from CH3, CH2F, CHF2 and / or CF3; and n can be from 1 to 20.

[0121] Examples of sulfonamide solvents include, but are not limited to, compounds of the following formula (8):

[0122] (8).

[0123] In formula (8), R1 to R3 can be the same or different and can be H, F, CF3 and / or C1-C10 alkyl, wherein the C1-C10 alkyl can be optionally substituted.

[0124] In some embodiments, one or more of the disclosed ether or sulfonamide solvent compounds may be combined with one or more lithium salts to produce an electrolyte composition. These electrolyte compositions can be used in any electrochemical energy storage system comprising (1) an electrochemical energy storage system containing silicon or SiOx as electrodes; (2) an electrochemical energy storage system containing lithium metal (or without an anode, in which case lithium is derived from the cathode and deposited on the exposed anode current collector during the first charge) as an anode; or (3) any lithium-ion battery containing graphite as an anode. In a further embodiment, the active material in the electrodes described above is at least 50% by weight Si (silicon predominant).

[0125] In some embodiments, two or more of the disclosed ether or sulfonamide solvent compounds are present in the electrolyte composition (co-solvent).

[0126] In some embodiments, the salt used with the ether or sulfonamide solvent compound is selected from lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium nitrate (LiNO3), and lithium perchlorate (LiClO4). The salt concentration can be 0.5 M, 0.8 M, 1 M, 1.2 M, 1.5 M, 2 M, 3 M, or 4 M or higher. In some embodiments, the concentration is from 0.5 M to 4 M. In other embodiments, the concentration is less than 1 M, for example, from 0.1 M to 0.7 M. When two or more salts are used (one may be the main component and the other may be a minor component), a lower concentration range is useful.

[0127] The electrolyte composition may contain >20% of the disclosed ether or sulfonamide solvent compound; in other embodiments, the electrolyte composition contains >50%, >80%, >90%, and about 100% of the disclosed ether or sulfonamide solvent compound. Furthermore, as described above, in some embodiments, the solvent for the electrolyte may be about 20 wt%, about 30 wt%, about 40 wt%, about 50 wt%, about 60 wt%, about 70 wt%, about 80 wt%, or about 90 wt% of the electrolyte composition. In some embodiments, the solvent may have a concentration of about 10 wt% to about 90 wt%, about 10 wt% to about 80 wt%, about 10 wt% to about 60 wt%, about 20 wt% to about 60 wt%, about 20 wt% to about 50 wt%, about 30 wt% to about 60 wt%, about 30 wt% to about 70 wt%, or about 30 wt% to about 50 wt%. The amount can be measured as a percentage of the total solvent.

[0128] In some embodiments, the electrolyte composition may have two or more components. In a further embodiment, the electrolyte composition may have a solvent and a lithium salt; in another embodiment, the electrolyte composition may have two or more solvents and may also contain one or more lithium salts; in a further embodiment, the electrolyte composition may have three or more solvents and may also contain one or more lithium salts.

[0129] Specific examples of ether and sulfonamide solvents include, but are not limited to, the following:

[0130] 4-Methyltetrahydropyran (4-mTHP); Dimethoxyethane (DME);

[0131] 1,1,2,2-Tetrafluoroethyl 2,2,3,3-Tetrafluoropropyl ether (TFTFPE);

[0132] Dimethyltrifluoromethanesulfonamide (DMT); and / or

[0133] CF3CH2OCH2CF3

[0134] Bis(2,2,2-trifluoroethyl) ether (BTFE).

[0135] In some embodiments, for example, compared to a lithium-ion battery comprising a conventionally available electrolyte composition and an anode having a composite electrode film according to one or more embodiments described herein, a lithium-ion battery comprising an electrolyte composition and an anode having a composite electrode film according to one or more embodiments described herein may exhibit reduced gas evolution and / or expansion at about room temperature (e.g., about 20°C to about 25°C) or high temperatures (e.g., temperatures up to about 85°C), increased cycle life at about room temperature or high temperatures, and / or reduced cell growth / electrolyte consumption per cycle. In some embodiments, a lithium-ion battery comprising an electrolyte composition and an anode having a composite electrode film according to one or more embodiments described herein may exhibit reduced gas evolution and / or expansion (e.g., compared to a lithium-ion battery comprising a conventionally available electrolyte composition and an anode having a composite electrode film according to one or more embodiments described herein) at a variety of temperatures the battery may be tested at, for example, at temperatures from about -20°C to about 130°C.

[0136] For example, undesirable gaseous byproducts may be generated during battery operation due to chemical reactions between the electrolyte of a lithium-ion battery and one or more other components (e.g., one or more components of the battery electrode). Excessive gas generation during lithium-ion battery operation can adversely affect battery performance and / or lead to mechanical and / or electrical failures. For example, undesirable chemical reactions between the electrolyte and one or more components of the anode may result in gas generation at levels that can mechanically (e.g., structurally deform) and / or electrochemically degrade the battery. The electrolyte compositions described herein can be advantageously used in energy storage devices. In some embodiments, the energy storage device may include a battery, a capacitor, and a battery-capacitor hybrid device. In some embodiments, the energy storage device comprises lithium. In some embodiments, the energy storage device may include at least one electrode, such as an anode and / or a cathode. In some embodiments, at least one electrode may be a Si-based electrode. In some embodiments, the Si-based electrode is a Si-dominant electrode, wherein silicon constitutes the majority (e.g., greater than 50% by weight) of the active material used in the electrode. In some embodiments, the energy storage device includes a separator. In some embodiments, the separator is located between a first electrode and a second electrode.

[0137] In some embodiments, the second electrode is a Si-dominant electrode as described herein. In some embodiments, the second electrode comprises a self-supporting composite membrane. In some embodiments, the composite membrane comprises greater than 0 wt% and less than about 95 wt% of silicon particles, and greater than 0 wt% and less than about 90 wt% of one or more types of carbon phases, wherein at least one of the one or more types of carbon phases is a substantially continuous phase holding the composite membrane together such that the silicon particles are distributed throughout the composite membrane.

[0138] In some embodiments, when cycled at a C-rate of >2C between an upper limit voltage of >4V and a lower cutoff voltage of <3.3V, the battery can be capable of performing at least 200 cycles with a cycle retention rate exceeding 80%. In other embodiments, when cycled at a C-rate of >2C between an upper limit voltage of >4V and a lower cutoff voltage of <3.3V, the battery can be capable of performing at least 200 cycles with a cycle retention rate exceeding 80%.

[0139] This document describes electrolyte compositions that provide improved performance for lithium-ion batteries. The electrolyte compositions may vary in the solvent used (and, when using a multi-solvent system), and / or the salt used. As described above, lithium-ion batteries comprising electrolyte compositions according to one or more embodiments described herein, and anodes and cathodes according to one or more embodiments described herein, can exhibit advantageous properties. Specifically, the electrolyte compositions disclosed herein provide one or more of the following benefits, particularly when the cell is cycled and stored at 100% state of charge (SOC) at high temperatures: (1) cycle life up to 80% capacity; (2) better high-temperature stability; (3) less gas evolution; (4) lower total cost; (5) improved total delivered energy up to 80% capacity; and / or (6) improved safety (lower flammability and less susceptibility to thermal runaway).

[0140] The benefits can be attributed to the improved chemical and electrochemical stability of the novel electrolyte chemicals, limiting significant degradation at the electrode / electrolyte interface. Specifically, considering the disclosed sulfonamide solvents, these provide one or more of the following benefits: (1) high chemical resistance; (2) stable interface with high-Ni cathodes; (3) stability against singlet oxygen (suppression of gas evolution); (4) improved anodic SEI properties (Li+ conductivity, formed without gas evolution, primarily inorganic properties); (5) improved safety (flame retardancy, etc.); and / or (6) high oxidative stability.

[0141] The lithium-ion battery used in the following experiments may include a Si-dominant anode and an NCM811 cathode; and the electrolyte composition described below. The cell may employ a 5-layer pouch cell design (5 layers of double-sided cathode and 6 layers of double-sided anode).

[0142] Figure 5 The performance of ether-based electrolytes (2 to 5) that differ from those of carbonate-based electrolytes (1) is shown in Table 1 below: Table 1

[0143] Compared with standard carbonate electrolyte (1), the above formulation can achieve an improvement in cycle life of more than 1.4x.

[0144] According to density functional theory (DFT) calculations (B3LYP / 6-31G) Fluorination of the cyclic ether, especially at the 1-position, leads to a significant decrease in HOMO, while the LUMO energy changes very little (see Table 2 below). This suggests the possibility of a significant improvement in oxidative stability while maintaining relatively high reducing stability.

[0145]

[0146] Tetrahydrofuran (THF)

[0147] 2-Fluoro-tetrahydrofuran (THF-1F).

[0148] Table 2

[0149] Table 3 provides an overview of the performance of the 5-layer Si / NCM811 pouch cell measured at room temperature (25°C) and high temperature (45°C), comparing the control electrolyte system vs. sulfonamide vs. sulfonamide + FEC electrolyte system. The electrolyte compositions used in this experiment are shown in Table 4.

[0150] Compared to standard carbonate electrolytes (control), the following formulation can achieve a cycle life improvement of more than 1.6x.

[0151] Table 3

[0152] Table 4

[0153] Figure 6The normalized discharge capacity retention of a 5-layer pouch cell based on a Si anode, NCM811 cathode, and control electrolyte (black), sulfonamide electrolyte (red), and sulfonamide + FEC electrolyte (green) is shown under room temperature and high temperature cycling. The compositions are listed in Table 4. Cycling scheme: 0.5 C (4.1 V) charge / 0.5 C (2.0 V) discharge.

[0154] Figure 7 Gas evolution analysis of a 5-layer Si / NCM811 pouch cell is shown, comparing a control electrolyte (black) vs. a sulfonamide electrolyte (red). From left to right: after cycling at room temperature at 75% state of health (SOH), after cycling at 45°C at 75% SOH, and after 4 weeks of storage at 4.1 V and 60°C. Cells containing the electrolyte composition (sulfonamide) of this invention show less gas evolution, as measured by cell thickness.

[0155] Table 5 shows the capacity recovery, comparing the control electrolyte (black) vs. sulfonamide electrolyte (red) for capacity recovery of 5-layer Si / NCM811 pouch cells during 4 weeks of storage at 100% SOC at 60°C.

[0156] Table 5

[0157] As used herein, the terms “circuit” and “circuit system” refer to physical electronic components (i.e., hardware) and any software and / or firmware (“code”) that can configure, be executed by, and / or otherwise associate with the hardware. As used herein, for example, a particular processor and memory may include a first “circuit” when executing a first line or more of code, and a second “circuit” when executing a second line or more of code. As used herein, “and / or” means any one or more items in a list connected by “and / or”. As an example, “x and / or y” means any element of the three-element set {(x), (y), (x, y)}. In other words, “x and / or y” means “one or both of x and y”. As another example, “x, y and / or z” means any element of the seven-element set {(x), (y), (z), (x, y), (x, z), (y, z), (x, y, z)}. In other words, "x, y, and / or z" means "one or more of x, y, and z". As used herein, the term "exemplary" means used as a non-limiting example, instance, or illustration. As used herein, the terms "for example" and "such as" introduce one or more non-limiting examples, instances, or illustrations. As used herein, a battery, circuit system, or device is "operable" to perform a function whenever said battery, circuit system, or device includes the necessary hardware and code (if required) or other elements to perform the function, regardless of whether the function's performance is disabled or not enabled (e.g., through user-configurable settings, factory tuning, configuration, etc.).

[0158] Although the invention has been described with reference to certain embodiments, those skilled in the art will understand that various changes and substitutions can be made without departing from the scope of the invention. Furthermore, many modifications can be made to adapt particular situations or materials to the teachings of the invention without departing from the scope of the invention. Therefore, the invention is not intended to be limited to the specific embodiments disclosed, but rather to include all embodiments falling within the scope of the appended claims.

Claims

1. An electrolyte composition for an energy storage device, wherein the electrolyte composition comprises one or more solvents and one or more lithium-containing salts; The one or more solvents mentioned above are cyclic ethers of formula (1) or formula (2): (1) or (2); Among them, R1 to R 10 The same or different, and selected from H, F, CF3 and C1-C10 alkyl groups, wherein the C1-C10 alkyl groups may optionally be substituted.

2. The electrolyte composition according to claim 1, wherein R1 is F; and R2 to R 10 It is H, F, CF3 or C1-C10 alkyl, and the C1-C10 alkyl may optionally be substituted.

3. The electrolyte composition according to claim 1, wherein the cyclic ether is tetrahydrofuran (THF) or 2-fluorotetrahydrofuran (THF-1F).

4. The electrolyte composition according to claim 1, wherein the cyclic ether is tetrahydropyran (THP) or 2-fluorotetrahydropyran (THP-1F).

5. The electrolyte composition according to claim 1, wherein the one or more lithium-containing salts are selected from lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium nitrate (LiNO3), lithium perchlorate (LiClO4), lithium difluoro(oxalate)borate (LiDFOB), and lithium bis(oxalate)borate (LiBOB).

6. The electrolyte composition according to claim 5, wherein the one or more lithium-containing salts are selected from lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluorophosphate (LiPF6), lithium nitrate (LiNO3), lithium difluoro(oxalate)borate (LiDFOB), and lithium bis(oxalate)borate (LiBOB).

7. An electrolyte composition for use in an energy storage device, wherein the electrolyte composition comprises one or more solvents and one or more lithium-containing salts; The one or more solvents mentioned therein are straight-chain ethers.

8. The electrolyte composition according to claim 7, wherein the straight-chain ether is of formula (3) or (4): (3) or (4); R1 to R4 may be the same or different, and are selected from H, F, CF3 and C1-C10 alkyl groups, wherein the C1-C10 alkyl groups may optionally be substituted.

9. The electrolyte composition according to claim 8, wherein R4 is a straight-chain or branched C1-C10 alkyl group, wherein the straight-chain or branched C1-C10 alkyl group is substituted with H, F or CF3.

10. The electrolyte composition according to claim 7, wherein the straight-chain ether is or .

11. The electrolyte composition according to claim 7, wherein the straight-chain ether is of formula (5), formula (6), or formula (7): 、 (5) (6) or (7); Each of the Rs may be the same or different and is selected from CH3, CH2F, CHF2 and CF3; and n is 1 to 20.

12. The electrolyte composition according to claim 7, wherein the one or more lithium-containing salts are selected from lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium nitrate (LiNO3), lithium perchlorate (LiClO4), lithium difluoro(oxalate)borate (LiDFOB), and lithium bis(oxalate)borate (LiBOB).

13. The electrolyte composition according to claim 12, wherein the one or more lithium-containing salts are selected from lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluorophosphate (LiPF6), lithium nitrate (LiNO3), lithium difluoro(oxalate)borate (LiDFOB), and lithium bis(oxalate)borate (LiBOB).

14. An electrolyte composition for use in an energy storage device, wherein the electrolyte composition comprises one or more solvents and one or more lithium-containing salts; The one or more solvents mentioned above are one or more ethers or sulfonamides: 4-Methyltetrahydropyran (4-mTHP), dimethoxyethane (DME) 1,1,2,2-Tetrafluoroethyl 2,2,3,3-Tetrafluoropropyl ether (TFTFPE) Dimethyltrifluoromethanesulfonamide (DMT) or CF3CH2OCH2CF3 Bis(2,2,2-trifluoroethyl) ether (BTFE).

15. The electrolyte composition according to claim 14, wherein the one or more lithium-containing salts are selected from lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium nitrate (LiNO3), and lithium perchlorate (LiClO4).

16. The electrolyte composition according to claim 15, wherein the one or more lithium-containing salts are selected from lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluorophosphate (LiPF6), and lithium nitrate (LiNO3).

17. An electrolyte composition for use in an energy storage device, wherein the electrolyte composition comprises one or more solvents and one or more lithium-containing salts; The one or more solvents mentioned above are sulfonamides of formula (8): (8) Each of R1 to R3 may be the same or different, and is selected from H, F, CF3 and C1-C10 alkyl groups, which may optionally be substituted.

18. The electrolyte composition according to claim 17, wherein the one or more lithium-containing salts are selected from lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium nitrate (LiNO3), lithium perchlorate (LiClO4), lithium difluoro(oxalate)borate (LiDFOB), and lithium bis(oxalate)borate (LiBOB).

19. The electrolyte composition according to claim 18, wherein the one or more lithium-containing salts are selected from lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluorophosphate (LiPF6), lithium nitrate (LiNO3), lithium difluoro(oxalate)borate (LiDFOB), and lithium bis(oxalate)borate (LiBOB).

20. The electrolyte composition according to claim 1, wherein the electrolyte composition further comprises one or more additives selected from FEC (fluoroethylene carbonate), VC (ethylene carbonate), VEC (vinyl ethylene carbonate), PS (1,3-propanesulfonate lactone), PES (prop-1-ene-1,3-sulfonate lactone), MMDS (methylene disulfonate), TMSP (tris(trimethylsilyl)phosphite), TMS (trimethylene sulfate), TMSO (3-trimethylsilyl-2-oxazolidinone), 1,4-BS (1,4-butyrylolactone), PMS (propargyl methanesulfonate), BP (biphenyl), DTD (1,3,2-dioxazothiophene 2,2-dioxide), and TAP (trimyl phosphate).

21. The electrolyte composition of claim 20, wherein the additive is present in an amount of about 0.1% to 30% by weight.

22. The electrolyte composition according to claim 1, wherein the electrolyte composition further comprises one or more additional components selected from the solvents EC (ethylene carbonate), FEC (fluoroethylene carbonate), PC (propylene carbonate), EMC (ethyl methyl carbonate), DMC (dimethyl carbonate), DEC (diethyl carbonate), GBL (γ-butyrolactone), MA (methyl acetate), EA (ethyl acetate), t-BC (trans-butenyl carbonate), and PMC (propyl methyl carbonate).

23. The electrolyte composition of claim 22, wherein the additional component is present in an amount of about 0.1% to 80% by weight.

Citation Information

Cited By

  • Electrolyte and lithium battery

    CN121355376A